Porcine reproductive and respiratory syndrome virus NADC30‐like strain accelerates Streptococcus suis serotype 2 infection in vivo and in vitro. Issue 2 (23rd December 2018) - Li, Jianda; Wang, Jinbao; Liu, Yueyue; Yang, Jie; Guo, Lihui; Ren, Sufang; Chen, Zhi; Liu, Zhaoshan; Zhang, Yuyu; Qiu, Wenbin; Li, Yubao; Zhang, Shujin; et al.
Abstract: Porcine reproductive and respiratory syndrome (PRRS), an economically significant pandemic disease, commonly results in increased impact of bacterial infections, including those by Streptococcus suis ( S. suis ). In recent years, PRRS virus (PRRSV) NADC30‐like strain has emerged in different regions of China, and coinfected with S. suis and PRRSV has also gradually increased in clinical performance. However, the mechanisms involved in host innate responses towards S. suis and their implications of coinfection with NADC30‐like strain remain unknown. Therefore, the pathogenicity of NADC30‐like strain and S. suis serotype 2 (SS2) coinfection in vivo and in vitro was investigated in this study. The results showed that NADC30‐like increased the invasion and proliferation of SS2 in blood and tissues, resulting in more severe pneumonia, myocarditis, and peritonitisas well as higher mortality rate in pigs. In vitro, NADC30‐like strain increased the invasion and survival of SS2 in porcine alveolar macrophages (PAM) cells, causing more drastic expression of inflammatory cytokines and activation of NF‐ĸB signalling. These results pave the way for understanding the interaction of S. suis with the swine immune system and their modulation in a viral coinfection.